Reversal of ophthalmic artery flow as a predictor of intracranial hemodynamic compromise: implication for prognosis of severe carotid stenosis. Issue 3 (24th December 2012) - Tsai, C.‐L.; Lee, J.‐T.; Cheng, C.‐A.; Liu, M.‐T.; Chen, C.‐Y.; Hu, H.‐H.; Peng, G.‐S.
Abstract : Background and purpose: High‐grade cervical carotid stenosis (70–99%) or occlusion often accompanies reversed ophthalmic artery flow (ROAF), but its potential clinical significances remain poor understood. This study assessed ROAF and the related variables caused by carotid hemodynamic compromise in patients with unilateral severe cervical carotid stenosis. Methods: The study consisted of 200 patients diagnosed as unilateral high‐grade cervical carotid stenosis/occlusion using ultrasonography. The hemodynamic parameters of 152 patients, excluding 48 with cervical carotid occlusion, were compared based on the presence of ROAF. Out of 200 patients, 159 underwent brain magnetic resonance imaging and were analysed for risk factors impacting functional outcomes including ROAF. Results: The patients ( n = 48) with internal carotid artery occlusion had significantly higher incidence (62.5%) of ROAF compared with that of 25.0% in those patients ( n = 152) with unilateral high‐grade carotid stenosis ( P < 0.001). In ROAF patients ( n = 38) with the unilateral high‐grade stenosis, a significant retrobulbar arteries hemodynamic difference was observed between the stenotic and non‐stenotic vessels. The patients ( n = 159) with history of stroke ( P = 0.035), ROAF ( P = 0.023) and intracranial stenosis ( P < 0.001) exhibited significantly higher incidence of poor functional outcome compared with the corresponding control groups. In the same patients ( n = 159), those with both cervical and intracranial stenosis showed sevenfold higher risk (OR, 7.60; 95% CI, 3.44–16.81) for ROAF than those with only cervical stenosis. Conclusions: ROAF may result from intracranial hemodynamic compromise. Patients with unilateral high‐grade cervical carotid stenosis/occlusion in combination with intracranial stenosis appear to be a significant risk factor for poor functional outcome and increased incidence of ROAF.